ANALISIS IMPLEMENTASI PROGRAM NASIONAL AGRARIA (PRONA) DI KABUPATEN LAMPUNG TENGAH - Elip Heldan; Selamet Sugiyanto (Universitas Bandar Lampung (UBL), 2018)
The National Agrarian Program is the government's commitment in providing services in the area of land devoted to the economically disadvantaged to medium term, so that the cost of the service is subsidized by the government. Given that sudsidi given by the government basically derived from the people, then the government has a moral obligation to provide the best service to the community. The purpose of this study are: (1) To analyze the implementation of the National Agrarian Program in Central Lampung Regency (2) For the effective implementation of the National Agrarian Program in Central Lampung Regency This study uses a type of qualitative research, with research informants that is representative of the District Land Office in Central Lampung and community representatives. Data were collected by interview, documentation and observation. Data were then analyzed qualitatively. The results showed: 1) Implementation of the National Agrarian Program in Central Lampung Regency implemented with activity data collection and processing of physical, data collection and processing juridical and bookkeeping rights, issuance of Certificates to provide legal certainty and protection to the rights holder on a field ground, data presentation physical and juridical, as well as storing a list of public and documents, namely as a means of proving the right, by identification and stored at the land Office (2) the effectiveness of implementation of National Agrarian Program in Central Lampung regency in the category quite effective , because there are still obstacles in the implementation viz. the frequent occurrence of refutation or objections from other parties to the land registration process carried out by the applicant, the applicant is difficult in completing the requirements for registration of land for the first time, and low public awareness of the law in the field of land. Besides the fact that the difference between physical and juridical documents, data from the history of the land is not complete, the deed chronology broken or lost and their land disputes and the absence of boundary markers in the measurement of ground by officers as well as the registration fee borne by the landowner.